Application of Creative Dance Arts to Improve Flexibility of Movement of Children Aged 4-5 Years - Ayu Sulistya Putri; Cicilia Ika Rahayu Nita; Ayu Asmah (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
Flexibility of movement is an important aspect in the gross motor development of early childhood, especially in the age range of 4-5 years. The results of initial observations at KB Golden Kids Bululawang showed that only 5 out of 14 children achieved completeness in flexibility of movement. This study aims to determine the application of creative dance art in improving children's flexibility of movement. The method used is Classroom Action Research (CAR) with two learning cycles, each consisting of the planning, implementation, observation, and reflection stages. Data collection techniques were carried out through observation and documentation. The results of the study showed an increase in children's flexibility of movement, which was marked by an increase in the average value of 58.03% in the first cycle with the category of Starting to Develop (MB), and increased to 77.08% in the second cycle with the category of Developing Very Well (BSB), this increase indicates that creative dance art can stimulate children's flexibility of movement. This study concludes that creative dance art can improve flexibility of movement in early childhood, and can be a fun and useful learning alternative for PAUD teachers.